2019
DOI: 10.1016/j.acap.2019.05.067
|View full text |Cite
|
Sign up to set email alerts
|

53. Development of Progress Note Assessment and Plan Evaluation (Pnape) Tool

Abstract: BACKGROUND: Quality improvement (QI) education is a requirement at all stages of medical education training. Pediatric training programs are required to assess their trainees on quality improvement reflection and knowledge as part of the Pediatric Milestones. However, there is currently no validated tool for use in pediatrics to assess reflection on quality improvement opportunities. The Mayo Evaluation of Reflection on Improvement Tool (MERIT) has been previously published with validity evidence for use in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…10 In a forthcoming validation study, we found an interrater reliability of κ = .89 (95% confidence interval: .68-.97) and a moderate to strong positive association between mean PNAPE and PDQI-9 scores (Pearson's r = .63, p = .027). 11 …”
Section: Methodsmentioning
confidence: 99%
“…10 In a forthcoming validation study, we found an interrater reliability of κ = .89 (95% confidence interval: .68-.97) and a moderate to strong positive association between mean PNAPE and PDQI-9 scores (Pearson's r = .63, p = .027). 11 …”
Section: Methodsmentioning
confidence: 99%